Application of machine learning methods and remote sensing data for crop yield forecasting - ZATSERKOVNYI, Vitaliy; VOROKH, Victor; HLOBA, Olga; LIASHCHENKO, Olesia; SIUIVA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. Forecasting agricultural crop yields has always been a complex task, particularly in the context of climate instability and increasing pressure on resources. Given the limitations of classical mathematical models in such a complex field as agricultural analytics, data-driven approaches and machine learning-based methods are becoming increasingly important. The combination of satellite imagery, agrochemical soil analysis, and artificial intelligence algorithms is particularly promising for building flexible and accurate forecasts. Methods. This study analyzes two agricultural fields located in different regions of Ukraine with varying natural conditions. A comprehensive dataset was collected, including topographic features (elevation, slope, topographic wetness index), spectral indices from Sentinel-2A and Landsat 8 satellites (specifically, NDMI and GNDVI), and soil chemical composition. Correlation analysis was used to identify which indicators are most closely associated with yield levels. Yield prediction models were developed using Random Forest and Gradient Boosting algorithms, adapted to field subplots of 5 ha and 1 ha. Results. The analysis revealed that vegetation condition and crop water balance (NDMI, GNDVI) are the most effective indicators in explaining yield variability. Meanwhile, surface temperature showed a clearly negative impact, suggesting potential heat stress during the grain filling periods. Gradient Boosting demonstrated particularly high sensitivity to spatial detail, reaching a prediction accuracy of R²=0.801 at the 1 ha grid level. In contrast, Random Forest proved to be a robust method with lower sensitivity to data scale. Conclusions. The study demonstrates that combining satellite imagery, soil analysis results, and machine learning methods can significantly improve the accuracy of crop yield prediction. The developed models incorporate vegetation indices along with factors describing crop growing conditions. A comparison of various algorithms was also conducted under different levels of spatial detail. The results indicate that the proposed approach can be effectively applied in precision agriculture, particularly for agronomic planning and crop monitoring.